Implementation of Educational Service Quality Management at Teladan Kertasemaya Vocational High School Indramayu - AK, M. Fahmi Rofiudlofir.; Khana, Muhammad Amar; Yafrizal, Moch. Varhana; Putranto, Hilmy Ahmad (Jurnal Ilmiah Profesi Pendidikan, 2024)
The purpose of this research was to reveal and describe how Teladan Kertasemaya Vocational High School in Indramayu Regency implement their management of educational service quality in terms of planning, controlling, and quality improvement. This study used a qualitative descriptive method with interviews, observation, and documentation instruments. The subjects were school stakeholders who played a role in managing the educational service quality at Teladan Kertasemaya Vocational High School. The collected data was then analyzed through qualitative data analysis, including data reduction, data presentation, and conclusion. The result of this research shows that Teladan Ketasemaya Vocational High School quality planning was conducted twice in an academic year, in January and June, considering several things such as the school budget, necessary resources, facilities, learning outcomes targets, the learning system, as well as the reward and punishment system. The quality control was conducted by taking care of all resources.  The quality improvement implemented at Teladan Kertasemaya Vocational High School has successfully achieved various achievements both in academic and non-academic fields in various regional and national-level competitions.